Solve -x-5y-z=211 11x+8y-5z=-213 -2x-2z=62

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Solve the third equation for x.

-2x - 2z = 62

-2x = 62 + 2z

x = (62 + 2z) / -2

x = -31 - z

Substitute this expression in for x in the first equation.

-x - 5y - z = 211

-(-31 - z) - 5y - z = 211

31 + z - 5y - z = 211

31 - 5y = 211

-5y = 180

y = 180 / -5

y = -36

Now substitute (-31 - z) in for x and -36 in for y in the second equation and solve for z.

11x + 8y - 5z = -213

11(-31 - z) + 8(-36) - 5z = -213

-341 - 11z - 288 - 5z = -213

-629 - 16z = -213

-16z = 416

z = -26

We know from the third equation that x = -31 - z.  Substitute -26 in for z and solve for x.

x = -31 - z

x = -31 - (-26)

x = -5

Solution:  {x = -5, y = -36, z = -26}

Check these answers using substitution.

-x - 5y - z = 211
-(-5) - 5(-36) - (-26) = 211
211 = 211

11x + 8y - 5z = -213
11(-5) + 8(-36) - 5(-26) = -213
-213 = -213

-2x - 2z = 62
-2(-5) - 2(-26) = 62
62 = 62

The solutions work in all three equations.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial